A 3D virtual library model: representing verbal and multimedia content in three dimensional space - Boda, István; Tóth, Erzsébet; Bényei, Miklós; Csont, István (Qualitative and Quantitative Methods in Libraries; Vol 4 No 4 (2015): December 2015 Issue, 2017)
In our paper we present a three dimensional model of a virtual library based on the presentation and navigation possibilities of the Virtual Collaboration Arena (VirCA) system. In the implementation of the virtual library model we selected Greek literary works from among others which were once available in the ancient Library of Alexandria. Using our developed system at present we can represent selected (ancient) texts and texts related to certain ancient authors and their life-work, image files attached to various texts in a given arrangement, in the three dimensional space of the VirCA system. We have implemented the virtual library model with a PHP/MySQL-based development providing a HTML/JavaScript-based search interface and XML-based search results which can be represented in the VirCA system.